Preparation and characterization of poly (butylene adipate-co-terephtalate)/ oil palm empty fruit bunch fiber biocomposites - Siyamak, Samira (2011)
During the last years, the interest in renewable and biodegradable materials has tremendously increased in the global community. The global market for renewable and biodegradable materials increases immensely due to societal awareness of the climate situation and the problems arise from thermoplastics. In this research, the oil palm empty fruit bunch (EFB) fiber was used as an interesting source of lignocellulosic filler for preparation of the cost effective and biodegradable composites. The aliphatic aromatic co-polyester poly(butylene adipate-co-terephthalate) PBAT (EcoflexTM), a fully biodegradable thermoplastic polymer was used as matrix. The aim of this research is to fabricate a new class of biocomposite based on PBAT/EFB fiber and to improve the new biocomposites’ performance by chemical modification using succinic anhydride (SAH) as coupling agent in presence and absence of dicumyl peroxide (DCP) and benzoyl peroxide (BPO) as initiator. For the composite preparation, several blends were prepared at different contents of filler and matrix using melt blending technique. The specimens for mechanical tests were prepared based on ASTM standards. The effects of fiber loading and coupling agent loading on thermal properties of biodegradable polymer composites were evaluated using thermal gravimetric analysis (TGA) and dynamic mechanical analysis (DMA). TGA was used to evaluate composite decomposition and stability whilst DMA was utilized to evaluate parameters such as the glass transition temperature, Tg, storage modulus, E' and loss modulus, E". Scanning Electron Microscopy (SEM) was used for morphological studies. The chemical structure of new biocomposite was also analyzed using Fourier Transform Infrared (FTIR) Spectroscopy technique. The water absorption test was used for composite moisture absorption determination and the burial test was used to biodegradation studies. The PBAT biocomposite reinforced with 40 (wt%) of EFB fiber showed the best mechanical properties compared to the other PBAT/EFB fiber biocomposites. Biocomposites treatment with 4 (wt%) of succinic anhydride (SAH) and 1 (wt%) of DCP improved both tensile and flexural strength as well as tensile and flexural modulus, whereas the biocomposites’ impact strength improvement was only marginal. The FTIR analyses proved the mechanical test results by presenting the evidences of successful esterification using SAH/DCP in biocomposites’ spectra. The SEM micrograph of the tensile fractured surfaces showed the improvement of fiber-matrix adhesion after using SAH. The TGA results showed that chemical modification using SAH/DCP improved the thermal stability of PBAT/EFB biocomposite. The DMA results showed the improvements of storage modulus as well as loss modulus and Tg of new composite modified by SAH. The water absorption test results indicated a decrease in moisture absorption trend of new biocomposite affected by (SAH) coupling agent compared to the untreated biocomposite. The biodegradation test observations showed a moderate increase in biological resistance of the modified biocomposites compare to the unmodified one.